Time‐course study of grape berry split using diffusion magnetic resonance imaging. (16th October 2015) - Dean, R.J.; Bobek, G.; Stait‐Gardner, T.; Clarke, S.J.; Rogiers, S.Y.; Price, W.S.
Abstract: Background and Aims: Fruit split is a well‐known source of fruit loss in viticulture. Previous investigations on this topic have focused on determining the factors that influence the occurrence of fruit split. The purpose of this study was to examine and characterise the immediate effect of fruit split on grape tissue structure using diffusion magnetic resonance imaging (MRI). Methods and Results: Thirty‐six ripe tablegrape berries were studied: 12 were assigned to a control group, 12 were wrapped in damp tissue and the remainder were wholly immersed in water. The berries were imaged over a period of 20 h with an MRI spectrometer. Grape berries that developed splits in the epidermis of sufficient length for imaging during this period exhibited an immediate increase in the mean apparent diffusivity in the pericarp tissue immediately surrounding these wounds. Further investigation determined that this increase in diffusivity was due to a loss of cell vitality. Physical trauma and oxygen shock were ruled out as the cause of cell death. Conclusions: Standing water on the grape berry surface during the occurrence of fruit split will quickly lead to pericarp cell death as a result of the osmotic imbibition of water through the wounds in the berry epidermis. Significance of the Study: The amount of standing water on the surface of split grape berries may be an important determinant of: (i) the cellular response of the fruit to this trauma; and (ii) the subsequent establishment of adventitious fruit pathogens.